DEVELOPMENT OF STORY-BASED TEACHING MATERIALS FOR ISLAMIC RELIGIOUS EDUCATION COURSES - Ondeng, Syarifuddin; Larissa, Dea; Rahman, Ananda Fathur; Bahraeni, Bahraeni; Usman, Usman (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
The dissemination of the development of story-based teaching materials at the University of West Sulawesi was carried out with a 4D model. The data were obtained based on student learning outcomes and student and lecturer responses. The profile of teaching materials consists of: (a) basic competencies, (b) indicators, (c) objectives, (d) concept maps, (e) materials, equipped with stories of each subject, (f) formative tests, and ( g) bibliography. The effectiveness test was declared complete individually and classically. The normalized gain value is included in the medium category with a value of 0.55 and the level of practicality through the lecturer's response is very good with a value of 3.58 and the student category is very good with a score of 3.64. Abstrak: Dilakukan desimasi pengembangan bahan ajar berbasis kisah di Universitas Sulawesi Barat dengan model 4D. Data diperoleh berdasarkan hasil belajar mahasiswa dan respon mahasiswa dan dosen. Profil bahan ajar terdiri terdiri atas: (a) kompetensi dasar, (b) indikator, (c) tujuan, (d) peta konsep, (e) materi, dilengkapi kisah masing-masing pokok bahasan, (f) test formatif, dan (g) daftar pustaka. Uji keefektifan dinyatakan tuntas secara individual maupun secara klasikal. Nilai Gain Ternormalisasi termasuk dalam kategori sedang dengan nilai 0.55 dan tingkat kepraktisan melalui respon dosen sangat baik dengan nilai 3.58 dan mahasiswa kategori sangat baik nilai 3.64.